Four cases of Japanese patients with psoriatic arthritis in whom effective treatments by anti‐tumor necrosis factor‐α drugs were evaluated by magnetic resonance imaging together with improvement of skin lesions. Issue 1 (26th November 2014) - Yonenaga, Takenori; Saeki, Hidehisa; Nakagawa, Hidemi; Fukuchi, Osamu; Umezawa, Yoshinori; Hayashi, Mitsuha; Ito, Toshihiro; Yanaba, Koichi; Tojyo, Shinjiro; Fukuda, Kunihiko
Abstract Because psoriatic skin lesions of psoriatic arthritis (PsA) usually precede the onset of joint symptom, dermatologists are in an ideal position to screen and find individuals with PsA early in the disease course. There have been no reports from the dermatology field evaluating the effect of anti‐tumor necrosis factor (TNF)‐α drugs on joint disorders using magnetic resonance imaging (MRI) in PsA patients. The purpose of this study was to elucidate the effectiveness of MRI in the evaluation of anti‐TNF‐α drugs on joint disease of Japanese PsA patients. Data were collected from four adult Japanese male PsA patients. MRI of the affected hand was performed at baseline and 1–7 months after infliximab or adalimumab treatment. T1‐weighted gadolinium‐enhanced images with fat suppression were acquired in the coronal, sagittal and/or axial planes. We determined the apparent improvement of synovitis, periarticular inflammation, tenosynovitis and/or bone marrow edema by MRI after anti‐TNF‐α treatments in all the patients together with the improvement of skin lesions. We also determined in one patient that these symptoms detected by MRI before treatment were alleviated within 1 month and had disappeared 6 months after treatment, suggesting the potentially early detection of the effect of anti‐TNF‐α drugs on joint disease. We present four cases of Japanese patients with PsA in whom effective treatments by anti‐TNF‐α drugs were evaluated by contrast‐enhanced MRI. This imaging enables dermatologists and radiologists to assess and monitor early inflammatory changes, and to grant PsA patients earlier access to modern treatment such as biologics.